Enhancing Students’ Writing Abilities on Descriptive Text by Using Spidergram Technique - Shary, Maria Yunita Nona (Indo-MathEdu Intellectuals Journal, 2025)
Writing is one of the ways people convey information and give their opinions on certain topic. As an indispensable part of language communication, writing becomes an important skill that students must master. The aim of the research is to Improve Students' Writing Ability on Descriptive Text by Using Spidergram Technique at the thenth Grade of SMAS Santo Petrus Kewapante. The participants were 12 students. The types of the research is a Classroom Action Research ( CAR ). In this research there are two cycles, and every cycle consisted of two meetings, and the end of each cycle the researcher conducts the test to measure the improvement of the students’ writing ability. The data are collected by using observation sheet, evaluation sheet and field note. In analyzing data the researcher describes the mean of the students based on their score to know the students’ improvement in every cycle. Each cycle consisted of planning, action, observation, and reflection. The class average score in cycle one was 63,58% with a percentage of 25%. The average value in cycle two was 66,92% with a percentage of 50%. And the average value in cycle three was 72,92% with a percentage of 75%. It can be seen from the class percentage that there was an increase from cycle one to cycle two by 25% and from cycle two to cycle three by 25%.